2023
DOI: 10.1039/d2fo02707k
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin attenuates sepsis-induced intestinal barrier injury by regulating neutrophil extracellular trap formation via the ROS/autophagy signaling pathway

Abstract: Hesperetin (HES), one of the major flavonoids that has various biological activities, such as anti-inflammatory and antioxidant activities, may preserve the intestinal barrier during sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…PMA promotes cell death by increasing chromatin loosening and incorporating the nuclear envelope into organelles, a process that occurs within a few hours ( 39 , 40 ). This process involves four key steps: (1) enhanced plasma membrane permeability, (2) accelerated disintegration of the nuclear envelope and cytoskeleton, (3) assembly of antimicrobial proteins onto chromatin scaffolds, and (4) decondensation of chromatin ( 41 ). In vitro experiments using isolated neutrophils treated with PMA have provided valuable mechanistic insights into lytic NET formation ( Figure 1 ), demonstrating that neutrophil activation is accompanied by the assembly and activation of a multicomponent nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and ROS ( 51 53 ).…”
Section: Nets Discovery Origin and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…PMA promotes cell death by increasing chromatin loosening and incorporating the nuclear envelope into organelles, a process that occurs within a few hours ( 39 , 40 ). This process involves four key steps: (1) enhanced plasma membrane permeability, (2) accelerated disintegration of the nuclear envelope and cytoskeleton, (3) assembly of antimicrobial proteins onto chromatin scaffolds, and (4) decondensation of chromatin ( 41 ). In vitro experiments using isolated neutrophils treated with PMA have provided valuable mechanistic insights into lytic NET formation ( Figure 1 ), demonstrating that neutrophil activation is accompanied by the assembly and activation of a multicomponent nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and ROS ( 51 53 ).…”
Section: Nets Discovery Origin and Diversitymentioning
confidence: 99%
“…In addition, G protein-coupled receptors (GPCRs) ( 54 ), CXC chemokine receptors (CXCRs) ( 55 ), toll-like receptors (TLRs) ( 56 , 57 ), and cytokine receptors contribute to this process. Hydrogen peroxide (H 2 O 2 ) is a robust oxidant generated by NADPH oxidase during the reduction of molecular oxygen through electron transfer, and it plays a crucial role in both NET and ROS generation ( 41 ). The correlation between neutrophil metabolism and ROS generation has been highlighted in mechanistic studies ( 58 , 59 ).…”
Section: Nets Discovery Origin and Diversitymentioning
confidence: 99%
“…Hesperetin (C 16 H 14 O 6 ) is the aglycone form of the flavanone glycoside hesperidin (C 28 H 34 O 15 ). It is a naturally occurring flavonoid found in citrus fruits such as oranges, grapes, and lemons and possesses antioxidant and anti‐inflammatory properties by regulating various host signaling pathways 22–24 . Recent studies have demonstrated the antiviral activity of hesperetin against herpes simplex virus type 1 (HSV‐1), poliovirus type 1, parainfluenza virus type 5, respiratory syncytial virus (RSV), influenza A virus, chikungunya virus (CHIKV), Zika virus (ZIKV), severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), yellow fever virus (YFV), Sindbis virus, and dengue virus (DENV) 25–32 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a naturally occurring flavonoid found in citrus fruits such as oranges, grapes, and lemons and possesses antioxidant and anti-inflammatory properties by regulating various host signaling pathways. [22][23][24] Recent studies have demonstrated the antiviral activity of hesperetin against herpes simplex virus type 1 (HSV-1), poliovirus type 1, parainfluenza virus type 5, respiratory syncytial virus (RSV), influenza A virus, chikungunya virus (CHIKV), Zika virus (ZIKV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), yellow fever virus (YFV), Sindbis virus, and dengue virus (DENV). [25][26][27][28][29][30][31][32] In this study, we extended the antiviral efficacy of hesperetin against poxviruses, besides providing insights into its potential mechanisms of action.…”
mentioning
confidence: 99%
“…As a result, blood flow is often redirected to vital organs such as the brain, lungs, and heart, which can cause ischemia, hypoxia, and reperfusion injury in the intestinal mucosa. During this process, a large amount of oxygen free radicals are produced, which can disrupt the formation and distribution of tight junctions between cells and cause damage to the intestinal epithelium ( 10 12 ). Simultaneously, the compromised intestinal microenvironment, weakened intestinal motility, and inadequate intestinal nutrition result in intestinal barrier dysfunction and increased permeability ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%